Exploration of Character Education Values of Local Culture “Leles” in the Context of Digital Education in East Manggarai - Heryon Bernard Mbuik; Cornelia Amanda Naitili (STKIP Taman Siswa Bima, 2024)
This research aims to explore the character education values of local culture “leles” in the context of digital education in East Manggarai. Given the challenges of globalization and rapid digitalization, it is important to assess how these traditional values can be maintained and integrated in the modern education system. The research used a descriptive qualitative method with a triangulation approach, involving observation, in-depth interviews, and documentation from participants consisting of teachers, students, and the local community. The results showed that “leles” cultural values, such as trust, social care, tolerance and responsibility, can be applied in digital education, enriching students' learning experience and strengthening their cultural identity. However, there are challenges in integrating these values into digital platforms, such as the technology gap, teachers' limited understanding in using technology, and conflicts between traditional values and digitalization. Therefore, this study suggests the need for teacher training, improved technological infrastructure and collaboration between the government, academics and communities to create digital education that respects local cultural values. The practical implications of this study suggest that digital education that integrates local values can help students develop a strong social character, deepen their understanding of culture and prepare them for a more competitive and dignified future life.